A 3D flexure–shear fiber element for modeling the seismic behavior of reinforced concrete columns. (15th June 2016) - Li, Zhong-Xian; Gao, Ying; Zhao, Qiuhong
Highlights: 3D flexure-shear fiber element is developed for shear-dominated RC columns. Plastic offsets are introduced to the 3D MCFT for modeling cyclic loads. Yassin's concrete model and Menegotto-Pinto's steel model are adopted in MCFT. Crack check imposed by the MCFT is avoided using Steven's method. Simulation results with 3D fiber element match well with RC column test results. Abstract: In order to model the nonlinear seismic behavior of reinforced concrete (RC) columns under a combined loading of axial force, biaxial bending moment and shear force, a displacement-based 3D flexure–shear fiber element accounting for the effect of shear–bending interaction is developed and presented. The element is based on the Timoshenko beam theory and the section is discretized into two types of fibers: fiber representing the longitudinal reinforcement bar and fiber representing the concrete with smeared stirrups. The constitutive law of the steel material follows the Menegotto–Pinto model, in which strain hardening and Bauschinger effects are considered. The 3D constitutive model for reinforced concrete follows the basic assumptions of the enhanced Modified Compression Field Theory (MCFT), where plastic strains are introduced as offsets to account for cyclic loading. The axial, shear and bending effects are fully coupled at both the section and the element level, since normal–shear interaction has been taken into account in the enhanced MCFT. The developed fiber element is implemented as a user-defined element in a FEA program, and validated with experimental results for columns under in-plane (2D) and bilateral (3D) cyclic loading. It is found that the proposed 3D flexural–shear fiber element is able to capture the complex hysteretic behavior of shear-dominated RC columns under 2D as well as 3D cyclic loading reasonably well.